2011
DOI: 10.1002/jmri.22726
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted and dynamic contrast‐enhanced MRI in evaluation of early treatment effects during neoadjuvant chemotherapy in breast cancer patients

Abstract: Purpose: To use dynamic contrast-enhanced (DCE) and diffusion-weighted (DW) MRI at 3 Tesla (T) for early evaluation of treatment effects in breast cancer patients undergoing neoadjuvant chemotherapy (NAC), and assess the reliability of DW-MRI.Materials and Methods: DW-and DCE-MRI acquisitions of 15 breast cancer patients were performed before and after one cycle of NAC. MRI tumor diameter and volume, apparent diffusion coefficient (ADC) and kinetic parameters (K trans , v e ) were derived. The reliability of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 41 publications
4
44
0
4
Order By: Relevance
“…Mean tumor ADC increased significantly as measured by both techniques after 3 weeks of therapy, which is in agreement with other studies of breast cancer patients that have reported significant increases in tumor ADC of a similar magnitude at early treatment time points (24) (6). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mean tumor ADC increased significantly as measured by both techniques after 3 weeks of therapy, which is in agreement with other studies of breast cancer patients that have reported significant increases in tumor ADC of a similar magnitude at early treatment time points (24) (6). …”
Section: Discussionsupporting
confidence: 91%
“…A similar relationship between pretreatment tumor ADC and tumor volume change was also found by Iacconi et al (10). However, other studies have found no correlation between pretreatment tumor ADC and final tumor volume change or pathologic complete response (4,13,24). As has been noted, the discrepancies in findings may be due to differences in DWI acquisition parameters, tumor ROI selection, and how tumor volume is calculated (26).…”
Section: Discussionmentioning
confidence: 82%
“…The DW-MRI approach is a highly sensitive tool that has demonstrated the potential to serve as an in vivo biomarker for early detection of tumor response prior to anatomic tumor size changes [36,4246]. Significant changes in tumor tissue water mobility have been detected in breast, brain, prostate and GI tract tumors following radiation and/or chemotherapy [36,4246].…”
Section: Discussionmentioning
confidence: 99%
“…The coupling of the diffusion imaging with the established morphological MRI provides superior evaluation of response to NAC compared with morphological MRI alone [68]. Changes in MRI-derived tumor diameter and ADC after only one cycle of NAC could provide a valuable tool for early evaluation of treatment effects [69, 70]. ADC measured after four cycles of NAC was shown to be a strong independent predictor of pCR [71].…”
Section: Early Response Predictors Using Different Mr Imaging Methodsmentioning
confidence: 99%